Bioengineered Kidney Models: Methods and Functional Assessments. Issue 4 (10th May 2021) - Rizki-Safitri, Astia; Traitteur, Tamara; Morizane, Ryuji
Abstract: Investigations into bioengineering kidneys have been extensively conducted owing to their potential for preclinical assays and regenerative medicine. Various approaches and methods have been developed to improve the structure and function of bioengineered kidneys. Assessments of functional properties confirm the adequacy of bioengineered kidneys for multipurpose translational applications. This review is to summarize the studies performed in kidney bioengineering in the past decade. We identified 84 original articles from PubMed and Mendeley with keywords of kidney organoid or kidney tissue engineering. Those were categorized into 5 groups based on their approach: de-/recellularization of kidney, reaggregation of kidney cells, kidney organoids, kidney in scaffolds, and kidney-on-a-chip. These models were physiologically assessed by filtration, tubular reabsorption/secretion, hormone production, and nephrotoxicity. We found that bioengineered kidney models have been developed from simple cell cultures to multicellular systems to recapitulate kidney function and diseases. Meanwhile, only about 50% of these studies conducted functional assessments on their kidney models. Factors including cell composition and organization are likely to alter the applicability of physiological assessments in bioengineered kidneys. Combined with recent technologies, physiological assessments importantly contribute to the improvement of the bioengineered kidney model toward repairing and refunctioning the damaged kidney.